2022
DOI: 10.1002/zamm.202200168
|View full text |Cite
|
Sign up to set email alerts
|

Cattaneo–Christov heat flux theory toward the magnetohydrodynamic micropolar hybrid nanofluid flow past a stretching/shrinking sheet with non‐uniform heat source/sink and thermal radiation

Abstract: In this investigation, a 2D flow of micropolar hybrid nanofluid (HNF) is considered over stretching/shrinking sheet. The magnetic effect is employed in a perpendicular direction to the surface of sheet. To improve the thermal conductivity of the fluid flow, the nanoparticles (NPs) of iron oxide and graphene oxide are mixed with water to obtain the HNF and water is used as a base fluidfalse(Fnormale3normalO4+GO/normalH2Ofalse)$\;( {{\rm{F}}{{\rm{e}}_3}{{\rm{O}}_4} + {\rm{GO}}/{{\rm{H}}_2}{\rm{O}}} )$. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Some advanced research topics covering the flow of nanofluid can be found in ref. [16][17][18][19][20][21][22][23][24]. Many scientists, especially in the last few decades, have become interested in the study of the flow via porous channels primarily because of the technology's widespread use in biological, industrial, and engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…Some advanced research topics covering the flow of nanofluid can be found in ref. [16][17][18][19][20][21][22][23][24]. Many scientists, especially in the last few decades, have become interested in the study of the flow via porous channels primarily because of the technology's widespread use in biological, industrial, and engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…Bachok et al [4] evaluated the unsteady boundary-layer flow of a nanofluid past a permeable stretching or shrinking surface. Algehyne et al [5] applied the Cattaneo-Christov heat flux theory to MHD micropolar hybrid nanofluid flow across a stretching or shrinking surface. In the presence of convective Nield boundary conditions, Liu et al [6] analyzed the Maxwell nanofluid over a linear stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Algehyne et al. [5] applied the Cattaneo‐Christov heat flux theory to MHD micropolar hybrid nanofluid flow across a stretching or shrinking surface. In the presence of convective Nield boundary conditions, Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Waini et al [10] studied the effects of radiation on the flow of a magnetohydrodynamic micropolar hybrid nanofluid with Joule heating and viscous dissipation effects across a contracting sheet. Algehyne et al [11] studied the Cattaneo-Christov heat flux theory over the magnetohydrodynamic micropolar hybrid nanofluid flow via a stretching/contraction sheet with a non-uniform heat source/sink and thermal radiation. Micropolar hybrid nanofluid M gO−Ag/water was studied by Sheikhzadeh et al [12] regarding flow and heat transport in a permeable channel.…”
mentioning
confidence: 99%